2013
DOI: 10.1007/s00251-013-0707-8
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity generated by ancient recombination-like events in the MHC of Indian rhesus macaques

Abstract: The Mamu-A, Mamu-B, and Mamu-DRB genes of the rhesus macaque show several levels of complexity such as allelic heterogeneity (polymorphism), copy number variation, differential segregation of genes/alleles present on a haplotype (diversity) and transcription level differences. A combination of techniques was implemented to screen a large panel of pedigreed Indian rhesus macaques (1,384 individuals representing the offspring of 137 founding animals) for haplotype diversity in an efficient and inexpensive manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 64 publications
(100 reference statements)
6
77
0
Order By: Relevance
“…In Indian rhesus macaques, it has been shown that the reshuffling of A, B , and DR region segments by recombination-like events can generate ‘new’ haplotypes that accumulated over long evolutionary time spans (Doxiadis et al 2013). Here, we also observed haplotypes (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indian rhesus macaques, it has been shown that the reshuffling of A, B , and DR region segments by recombination-like events can generate ‘new’ haplotypes that accumulated over long evolutionary time spans (Doxiadis et al 2013). Here, we also observed haplotypes (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinations within one region like the B region, however, which may be the reason for such patchwork haplotypes, have not often been observed when using Sanger sequencing (de Groot et al 2014; Doxiadis et al 2013). These are more easily visible with high resolution NGS techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, in most species, there is a strong evolutionary pressure to maintain old allelic variation within MHC genes (trans-species polymorphism 3, 4, 9 ), which, if anything, is likely to slow down speciation rates because it increases the required size of the founder population 9 . If old allelic or haplotype variation can’t be maintained because of rapid speciation through small founder populations, it can be speculated that a species might benefit from an enhanced capacity for the creation of new MHC allelic and/or haplotype variation by duplications/deletions and recombination 10 between a high number of linked MHC gene copies. However, in that scenario it wouldn’t be the MHC organization which drives the speciation rate, as suggested by Malmstrøm et al 1 , but the other way around.…”
Section: Correspondencementioning
confidence: 99%
“…For animals from the NEPRC colony, additional high-resolution sequencing was done using Roche 454 technologies on blood-derived lymphocyte cDNA Wiseman et al, 2013). In the case of the animals of BPRC, additional high-resolution Sanger sequencing had been performed beforehand and published previously (Otting et al, 2005;Doxiadis et al, 2013). Since the animals were members of breeding colonies, kinship coefficients and/or pedigrees of the animals are known, and some MHC haplotypes could be defined as well by segregation analysis.…”
Section: Mhc Typingmentioning
confidence: 99%